Fecal High-Mobility Group Box 1 as a Marker of Early Stage of Necrotizing Enterocolitis in Preterm Neonates - Vitali, Roberta; Terrin, Gianluca; Palone, Francesca; Laudadio, Ilaria; Cucchiara, Salvatore; Boscarino, Giovanni; Di Chiara, Maria; Stronati, Laura (Frontiers in Pediatrics, 2021)
Introduction: An early diagnosis of necrotizing enterocolitis (NEC), a major gastrointestinal emergency in preterm newborns, is crucial to improve diagnostic approach and prognosis. We evaluated whether fecal high mobility group box protein 1 (HMGB1) may early identify preterms at risk of developing NEC. Materials and Methods: A case-control study including neonates admitted at the Neonatal Intensive Care Unit (NICU) of the Sapienza University Hospital “Umberto I” in Rome, from July 2015 to December 2016. Stool samples obtained from Cases (preterm newborns with NEC) and Controls (newborns without NEC), were collected at the enrolment (T0) and within 7-14 days after the first sample collection (T1). HMGB1, extracted and measured with western blot, was reported as densitometry units (DUS). Results: HMGB1 levels in 30 Cases (n= 28 - Bell Stage 1, n = 2 Bell Stage 2) were higher (T0: 21462 DUS, 95% CI 16370-26553 DUS - T1: 17533 DUS, 95% CI 13052-22014 DUS) than in 30 preterm Controls (T0: 9446 DUS, 95% CI 6147-12746 DUS - T1: 9261 DUS, 95% CI 5126-13396 DUS, p < 0.001). Preterm newborns showed significant higher levels of HMGB1 (15690 DUS, 95% CI 11929-19451 DUS) in comparison with 30 full term neonates with birth weight > 2500 g (6599 DUS, 95% CI 3141-10058 DUS, p = 0.003). Multivariate analysis showed that the risk of NEC was significantly (p = 0.012) related to the HMGB1 fecal levels at T0. Conclusions: We suggest fecal HMGB1 as a reliable marker of early NEC in preterm neonates. This study supports further investigation on the role of fecal HMGB1 assessment in managing preterm newborns at risk of NEC. Further studies are advocated to evaluate diagnostic accuracy of this marker in more severe forms of the disease.